Model Manajemen Pemulihan Lingkungan Permukiman di Propinsi Aceh Pasca Tsunami - Pamekas, R. (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
Managing the recovery for the Environmental Settlement of Aceh post Tsunami, is not the easy task. Meanwhile, the aplication of the existing instrument that had been used to controll the economic program development had a significant constrains. Therefore, there is a need to develope a more practical instruments to guide the recovery program. This research is looking for the alternative instrument that suitable for the purposes. The so called management model for the recovery of enviromental settlement has been developed using the taxonomic method. Thhe developed instrument representing four recovery aspects namely vital need, social services, infrastructure and livelihood, addapting the selected 35 variables. Using the developed model, the progress of the designated four recovery aspect is evaluated. The results has been compared to the level damage environment. The recovery evaluation result concluded that the weigh of recovery development during 2005-2006 reaching to 46,5% with the recovery effectifity (EP_PL) of 138,39. The EP_PL greater than 100% indicating the effectiveness of the recovery as well as the disaster risk management program.